THE STIGMATIZATION OF COLORECTAL CANCER IN SOCIETY - de Simoni, Lívia (Health and Society, 2023)
Introduction: Although CRC is the main malignant neoplasm of the gastrointestinal tract and the third most typical type of cancer in the world, little is discussed about its morbidity and mortality. Because the lack of visibility does not provide an adequate budget for preventive health policies, most diagnoses do not occur in the early stages of the disease, which not only makes it more expensive, but also makes the therapeutic process difficult for the patient for the health team. To analyze the insufficient prevention of colorectal cancer. Objectives: to identify CRC mortality and relate it to the lack of prevention and information about the disease. Methodology: literature review that will be carried out through already published material made at the University of Ribeirão Preto. It will be an observational study that will establish correlations between the social and scientific aspects of colorectal cancer.